2022
DOI: 10.52567/pjsr.v4i1.344
|View full text |Cite
|
Sign up to set email alerts
|

Initial Psychometric Properties of General Functioning of Family Scale (Urdu Version)

Abstract: The Family Functioning Scale has been widely utilized in the literature to determine whether a family is healthy or dysfunctional. The current study aimed to translate the Family Functioning scale into the Urdu language and find out its initial psychometric properties on the Pakistani population. The measure was translated from English to the Urdu language by following standardized procedures. Cross-language validation was assessed by comparing the scores of a bilingual sample, (n=40) of 20 males and 20 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The link between family support and subjective well-being has been strongly supported by numerous studies (Huang & Zhang, 2022;Kareem et al, 2022;Leung et al 2020). Alshammari et al (2021) found that the perception of family support acts as a safeguarding component and is crucial in promoting subjective well-being in terms of satisfaction with life and perceived happiness in adolescents.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The link between family support and subjective well-being has been strongly supported by numerous studies (Huang & Zhang, 2022;Kareem et al, 2022;Leung et al 2020). Alshammari et al (2021) found that the perception of family support acts as a safeguarding component and is crucial in promoting subjective well-being in terms of satisfaction with life and perceived happiness in adolescents.…”
Section: Literature Reviewmentioning
confidence: 93%